2013
DOI: 10.1177/197140091302600109
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Labyrinthine Concussion in a Patient with Sensorineural Hearing Loss

Abstract: Blunt head trauma without any temporal bone fracture or longitudinal temporal bone fracture, with an associated fracture of the labyrinth may cause labyrinthine injury with sensor neural hearing loss and vertigo because of a concussive injury to the membranous labyrinth. Sudden sensory neural hearing loss is relatively frequent. In most cases, the etiology is not discovered. One of the possible causes for sudden deafness is inner labyrinth bleeding or concussion, which were difficult to diagnose before the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
(13 reference statements)
2
13
1
1
Order By: Relevance
“…Peripheral impairment is as a result of damage to the peripheral end organ (labyrinth) and/or the eighth cranial nerve, both of which can be traumatised by forces in the cranial cavity 15 16. Zhou and Brodsky17 recently reported that 90% of a series of 42 children with sport-related concussion had a vestibular or balance deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral impairment is as a result of damage to the peripheral end organ (labyrinth) and/or the eighth cranial nerve, both of which can be traumatised by forces in the cranial cavity 15 16. Zhou and Brodsky17 recently reported that 90% of a series of 42 children with sport-related concussion had a vestibular or balance deficit.…”
Section: Introductionmentioning
confidence: 99%
“…A subclassification can be made regarding labyrinthine concussion. If there is an isolated damage to the inner ear it would be a cochlear labyrinthine concussion and if the damage involves the otolith organ a vestibular labyrinthine concussion would be the preferable designation [ 8 , 9 ]. Labyrinthine concussion in most cases involves a SNHL with a notch in the 4–6 kHz resembling acoustic trauma, positional vertigo, or tinnitus [ 7 , 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A benign paroxysmal positional vertigo may also result from head trauma but vertigo must be present as the name indicates and no hearing loss is seen [ 7 ]. Another possibility is an isolated eighth nerve stretch injury which may be assessed by tests such as vestibular evoked myogenic potentials (VEMPs) or a severe crush injury or nerve transaction which is extremely rare and might be evaluated with a “promontory examination” test or a brainstem evoked response audiometry (BERA) [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have described degeneration of the vestibular sensory epithelia, in addition to degenerative changes of Scarpa's ganglion cells (ScGCs) . Although many mechanisms of vestibular dysfunction after head injury have been proposed in the literature, there are few reports that specifically address inner ear changes in humans …”
Section: Introductionmentioning
confidence: 99%
“…40 Although many mechanisms of vestibular dysfunction after head injury have been proposed in the literature, there are few reports that specifically address inner ear changes in humans. 28,[41][42][43][44] Taken together, whereas vestibular dysfunction secondary to head injury with TBF is a recognized clinical phenomenon, the precise mechanism remains largely unknown. Herein, we hypothesize that there is degeneration of peripheral vestibular organs, including the membranous labyrinth and ScGCs, following TBF.…”
Section: Introductionmentioning
confidence: 99%